2020
DOI: 10.1371/journal.pone.0244125
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and risk factors for severe inpatients with COVID-19: A retrospective study in China

Abstract: Background A worldwide outbreak of coronavirus disease (COVID-19), since 2019, has brought a disaster to people all over the world. Many researchers carried out clinical epidemiological studies on patients with COVID-19 previously, but risk factors for patients with different levels of severity are still unclear. Methods 562 patients with laboratory-confirmed COVID-19 from 12 hospitals in China were included in this retrospective study. Related clinical information, therapies, and imaging data were extracted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 40 publications
4
10
0
1
Order By: Relevance
“…Similarly, for ICU admission, while not statistically significant the pooled point estimate suggests a possible 21% increased risk of ICU admission from COVID-19 for people with asthma (95% CI −3% to 51%). One study from China (Wang [ 40 ]) and another from Kuwait (Almazeedi [ 41 ]) reported a risk ratio of 5.16 and 4.08 respectively, far greater than in other studies. These differences in risk may be linked to resource allocation and availability or difference in vulnerability due to ethnicity or other environmental factors.…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, for ICU admission, while not statistically significant the pooled point estimate suggests a possible 21% increased risk of ICU admission from COVID-19 for people with asthma (95% CI −3% to 51%). One study from China (Wang [ 40 ]) and another from Kuwait (Almazeedi [ 41 ]) reported a risk ratio of 5.16 and 4.08 respectively, far greater than in other studies. These differences in risk may be linked to resource allocation and availability or difference in vulnerability due to ethnicity or other environmental factors.…”
Section: Discussionmentioning
confidence: 92%
“…Eleven studies were retrospective [ 30 32 , 34 37 , 39 42 ], whilst the remaining two were prospective [ 33 , 38 ]. Endpoints included disease severity based on current clinical guidelines (8 studies) [ 31 , 33 35 , 37 , 39 , 40 , 42 ], disease progression (one study) [ 38 ] and occurrence of acute respiratory distress syndrome (ARDS) (one study) [ 36 ], and survival status (4 studies) [ 30 , 32 , 36 , 41 ]. Only two studies reported the presence of AKI [ 32 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…2 . In all studies, patients with high severity or non-survivor status had higher HBDH concentrations when compared to those with low severity or survivor status (mean difference range, 0.04 to 2.45), although the difference was not statistically significant in two studies [ 40 , 53 ]. The pooled results confirmed that HBDH concentrations on admission were significantly higher in patients with high severity or non-survivor status (SMD = 0.90, 95% CI 0.74 to 1.07, p < 0.001) (Fig.…”
Section: Resultsmentioning
confidence: 94%